Evaluation Of Marine Pollution (MARPOL) 73/78 Annex I-VI Policy on Maritime Environmental Protection in Indonesia Case Study on Traffic Separation Scheme (TSS) Strait of Malacca and Singapore - Wuryantari, Oktima; Pahala, Yosi; Lasse, D.A (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The Straits of Malacca and Singapore are the second busiest routes in the world that are used as international navigation routes that have the potential to be contaminated by cross-border oil spills. Various international legal instruments such as MARPOL 73/78 Annex I to VI regulate the prevention, reduction and control of pollution at sea. This study attempts to further evaluate the policies taken by Indonesia in order to control pollution in the Straits of Malacca and Singapore due to ship accidents. To overcome this problem, Indonesia as a country of law needs to immediately consider accommodation and integration of policy elements in determining laws and regulations, especially those related to maritime environmental protection law.